Is Social Capital Determinant in Developing Islamic Microfinance Institutions? - Imam Subchi; Asep Saepudin Jahar; Riris Aishah Prasetyowati (ETIKONOMI, 2024)
Research Originality: One of the Islamic Microfinance Institutions (IMFI) was  Baitul mal wa Tanwil (BMT) which generally has a program using the group loan methodology which is seen as utilizing existing social capital, manifested in personal relationships and networks.Research Objectives: This study aims to examine the impact of social capital factors on BMT business as an IMFI covering cultural values, religious traditions, people's world views, geographical characteristics, work ethic, institutions, and social networks.Research Methods: This study uses a mixed method explanatory with a qualitative method for testing the level of importance using the Analytic Process Hierarchy (AHP) f  or the best priority in social capital factors and the ideal IMFI based on expert opinions as facilitators.Empirical Result: This result shows that the seven social capital factors at IMFI can be applied and considered applicable in developing business. The main priority factors are institutions and religious traditions. The IMFI that consistently applies social capital factors in developing IMFI business is BMT Bringhardjo (Yogyakarta) although it has not yet reached the maximum value. The determinants of social capital in the IMFIs business are considerably used to determine the IMFIs business development. It provides that the seven social capital factors at IMFI can be applied and considered applicable in developing business.Implications: The main priority factors are institutions and religious traditions. Investigating one of the IMFI was Baitul mal wa Tanwil that consistently applies social capital factors in developing IMFI business as a business that empowers social capital as a guarantee feasibility and business feasibility from micro communities that have so far been un-bankable. JEL Classification: D02, D04, O14How to Cite:Subchi, I., Jahar, A. S., & Prasetyowati, R. A.. (2024). Is Social Capital Determinant in Developing Islamic Microfinance Institutions. Etikonomi, 23(1), 233 – 248. https://doi.org/10.15408/etk.v23i1.31769.